Electronic structure based design of thin film metallic glasses with superior fracture toughness. (15th January 2020) - Evertz, Simon; Kirchlechner, Ines; Soler, Rafael; Kirchlechner, Christoph; Kontis, Paraskevas; Bednarcik, Jozef; Gault, Baptiste; Dehm, Gerhard; Raabe, Dierk; Schneider, Jochen M.
Abstract: High fracture toughness is crucial for the application of metallic glasses as structural materials to avoid catastrophic failure of the material in a brittle manner. One fingerprint for fracture toughness in metallic glasses is the fraction of hybridized bonds, which is affected by alloying Pd57.4 Al23.5 Y7.8 M11.3 with M = Fe, Ni, Co, Cu, Os, Ir, Pt, and Au. It is shown that experimental fracture toughness data is correlated to the fraction of hybridized bonds which scale with the localized bonds at the Fermi level. Thus, the localized bonds at the Fermi level are utilized quantitatively as a measure for fracture toughness. Based on ab initio calculations, the minimum fraction of hybridized bonds was identified for Pd57.4 Al23.5 Y7.8 Ni11.3 . According to the ansatz that the crystal orbital overlap population at the Fermi level scales with fracture toughness, for Pd57.4 Al23.5 Y7.8 Ni11.3 a value of around 95 ± 20 MPa·m 0.5 is predicted quantitatively for the first time. Consistent with this prediction, in micro-mechanical beam bending experiments Pd57.4 Al23.5 Y7.8 Ni11.3 thin films show pronounced plasticity and absence of crack growth. Graphical abstract: Unlabelled Image Highlights: A model to quantitatively predict the fracture toughness based on the orbital overlap at the Fermi is introduced. The toughness of Pd57.4 Al23.5 Y7.8 Ni11.3 metallic glass is predicted to be 95 ± 20 MPa·m 0.5 . Pd57.4 Al23.5 Y7.8 Ni11.3 metallic glasses show pronounced plasticity and absence of crack growth in micro-mechanical cantilever bending experiments consistent with the predicted toughness.